Can diabetes with controlled glycemic status cause placental changes and affect foetal outcome? A histomorphology study from a tertiary care centre from Eastern India - Mishra, Poonam; Rihal Chakrabarti, Preeti (International Journal of Medical Research and Review, 2017)
Background: Normal foetal development and postnatal survival depends on healthy placenta. The adverse effects of diabetes on pregnancy and related foetal outcomes are well established and through this study we have attempted to study the intensity of damage caused, by examining the gross and microscopic features of placenta along with histochemical changes. Material and Methods: This was a prospective study undertaken in a tertiary teaching hospital in which a total of 80 cases of term pregnancy were studied, out of which 40 were from diabetic mothers and 40 were from non diabetic mothers. Biochemical parameters of all the cases were studied. All placenta were examined on the basis of gross features, histological & histochemical changes. Results: In the present study, it was noted that gross morphology of placenta was not much altered between diabetic and normal mothers but showed marked variation in the histological findings. On microscopic examination, marked basement membrane thickening, vascular proliferation, chorangiosis, syncytial knots, villous fibrosis and edema were noted among diabetic mothers and most common postnatal complication of newborns among diabetic mothers was macrosomia. Conclusion: This study highlights the impact of gestational and pregestational diabetes mellitus on placenta as observed by the magnitude of histological changes inspite of having controlled glycemic status either by diet or insulin and associated postnatal morbidities of newborns.